Peran MSDM Komunitas Lokal Dalam Menjaga Kelestarian Desa Adat Panglipuran dan Regenerasi Budaya - Eka Puji Lestari; Sabrina Willa Intana; Ivando, Ivando Ari Wibowo; Arum Agustiani; Lina Indah Lestari; Ihda Nor Rohmah (Jurnal Ilmiah Ekonomika & Sains, 2025)
Abstract, This study aims to analyze the role of local community-based Human Resource Management (HRM) in preserving sustainability and ensuring cultural regeneration in Panglipuran Village, Bali. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The focus of the study is on how the community, as the main human resource, manages tourism, maintains environmental cleanliness, and passes on cultural values to the younger generation. The findings reveal that the people of Panglipuran Village apply a customary system (awig-awig) that effectively sustains the village’s environment and cultural identity. Key strategies include limiting the number of tourists, practicing communal cooperation in maintaining cleanliness, and allocating tourism revenue to cultural preservation and facility development. Moreover, cultural regeneration is implemented by involving young generations in traditional ceremonies, non-formal education, as well as arts and handicraft training. The conclusion of this research emphasizes that Panglipuran’s success is not solely based on its cultural attractiveness but also on the participatory and local wisdom-based management of community human resources. These findings are expected to serve as a model for other tourism villages in developing sustainable community-based tourism.